It is currently 19 Nov 2017, 01:55

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

Let x and y be the solutions of the equation a^2+3a-1=0

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
Director
Director
avatar
P
Joined: 25 Feb 2013
Posts: 542

Kudos [?]: 247 [0], given: 33

Location: India
Schools: Mannheim"19 (S)
GPA: 3.82
GMAT ToolKit User Reviews Badge
Let x and y be the solutions of the equation a^2+3a-1=0 [#permalink]

Show Tags

New post 16 Sep 2017, 09:55
00:00
A
B
C
D
E

Difficulty:

  75% (hard)

Question Stats:

36% (03:33) correct 64% (02:27) wrong based on 14 sessions

HideShow timer Statistics

Let \(x\) and \(y\) be the solutions of the equation \(a^2+3a-1=0\). If \(P_n\) \(= x^n+y^n\) for \(n≥0\), then, for \(n≥2\), \(P_n =\)

A) \(-3P_{n-1} + P_{n-2}\)

B) \(3P_{n-1} + P_{n-2}\)

C) \(-P_{n-1} + P_{n-2}\)

D) \(P_{n-1} + 3P_{n-2}\)

E) \(P_{n-1} + P_{n-2}\)
[Reveal] Spoiler: OA

Kudos [?]: 247 [0], given: 33

Senior Manager
Senior Manager
User avatar
G
Joined: 02 Jul 2017
Posts: 269

Kudos [?]: 80 [0], given: 65

Location: India
GMAT ToolKit User CAT Tests
Let x and y be the solutions of the equation a^2+3a-1=0 [#permalink]

Show Tags

New post 16 Sep 2017, 11:24
I am not sure about shortcut method. But find below the method i used:

\(a^2+3a−1=0 => x+y = \frac{-3}{1} = -3\) and \(xy=\frac{-1}{1}=-1\) ( By sum and product of quadratic equation formula)

\(P_n =x^n+y^n\) \(n≥0\)

\(P_1 = x+y = -3\)
\(P_2 = x^2+y^2 = x^2+y^2+2xy-2xy = (x+y)^2-2xy = (-3)^2-2*(-1) = 11\)
\(P_3 =x^3+y^3 =x^3+y^3+3xy(x+y)-3xy(x+y)=(x+y)^3-3xy(x+y) =-36\)

Now with respect to \(P_3\) =>\(P_2 =P_{n-1}\) and \(P_1=P_{n-2}\)
but putting values we got \(P_3 =-36 = -3*(11)+(-3) = -3*P_{n-1}+P_{n-2}\)

Answer: A

Last edited by Nikkb on 16 Sep 2017, 13:02, edited 1 time in total.

Kudos [?]: 80 [0], given: 65

Director
Director
avatar
P
Joined: 25 Feb 2013
Posts: 542

Kudos [?]: 247 [0], given: 33

Location: India
Schools: Mannheim"19 (S)
GPA: 3.82
GMAT ToolKit User Reviews Badge
Re: Let x and y be the solutions of the equation a^2+3a-1=0 [#permalink]

Show Tags

New post 16 Sep 2017, 12:27
Nikkb wrote:
I am not sure about shortcut method. But find below the method i used:

\(a^2+3a−1=0 => x+y = \frac{-3}{1} = -3\) and \(xy=\frac{-1}{1}=-1\) ( By sum and product of quadratic equation formula)

\(Pn =x^n+y^n\) \(n≥0\)

\(p1 = x+y = -3\)
\(p2 = x^2+y^2 = x^2+y^2+2xy-2xy = (x+y)^2-2xy = (-3)^2-2*(-1) = 11\)
\(p3 =x^3+y^3 =x^3+y^3+3xy(x+y)-3xy(x+y)=(x+y)^3-3xy(x+y) =-36\)

Now for p3 =>\(p2 =p(n-1)\) and \(p1=p(n-2)\)
but putting values we got \(p3 =-36 = -3*(11)+(-3) = -3*p(n-1)+p(n-1)\)

Answer: A


Hi Nikkb,

We don't need a short-cut method here as the question can be solved in less than 2 minutes. Your approach is correct, however calculations could be made bit simpler to save time.

As you have rightly mentioned: Sum of roots, \(x+y = -3\) and Product of roots, \(xy=-1\)

Now we need to find \(P_n\) for \(n≥2\). This can be done by simply finding \(P_2\)

If you observe all answer choices have only \(P_{n-1}\) and \(P_{n-2}\). Hence we need to find \(P_1\) & \(P_0\)

\(P_0\) \(= x^0+y^0 = 1+1 =2\)

\(P_1\) \(= x^1+y^1 = x+y=-3\)

\(P_2\) \(=x^2+y^2 = (x+y)^2-2xy = (-3)^2-2*-1= -3*-3+2 =\) \(-3P_1\) \(+ P_0\)

Or \(P_n\) \(= −3P_{n−1}\) \(+ P_{n−2}\)

Hence Option A

Kudos [?]: 247 [0], given: 33

Senior Manager
Senior Manager
User avatar
G
Joined: 02 Jul 2017
Posts: 269

Kudos [?]: 80 [0], given: 65

Location: India
GMAT ToolKit User CAT Tests
Let x and y be the solutions of the equation a^2+3a-1=0 [#permalink]

Show Tags

New post 16 Sep 2017, 12:31
niks18 wrote:
Nikkb wrote:
I am not sure about shortcut method. But find below the method i used:

\(a^2+3a−1=0 => x+y = \frac{-3}{1} = -3\) and \(xy=\frac{-1}{1}=-1\) ( By sum and product of quadratic equation formula)

\(Pn =x^n+y^n\) \(n≥0\)

\(p1 = x+y = -3\)
\(p2 = x^2+y^2 = x^2+y^2+2xy-2xy = (x+y)^2-2xy = (-3)^2-2*(-1) = 11\)
\(p3 =x^3+y^3 =x^3+y^3+3xy(x+y)-3xy(x+y)=(x+y)^3-3xy(x+y) =-36\)

Now for p3 =>\(p2 =p(n-1)\) and \(p1=p(n-2)\)
but putting values we got \(p3 =-36 = -3*(11)+(-3) = -3*p(n-1)+p(n-1)\)

Answer: A


Hi Nikkb,

We don't need a short-cut method here as the question can be solved in less than 2 minutes. Your approach is correct, however calculations could be made bit simpler to save time.

As you have rightly mentioned: Sum of roots, \(x+y = -3\) and Product of roots, \(xy=-1\)

Now we need to find \(P_n\) for \(n≥2\). This can be done by simply finding \(P_2\)

If you observe all answer choices have only \(P_{n-1}\) and \(P_{n-2}\). Hence we need to find \(P_1\) & \(P_0\)

\(P_0\) \(= x^0+y^0 = 1+1 =2\)

\(P_1\) \(= x^1+y^1 = x+y=-3\)

\(P_2\) \(=x^2+y^2 = (x+y)^2-2xy = (-3)^2-2*-1= -3*-3+2 =\) \(-3P_1\) \(+ P_0\)

Or \(P_n\) \(= −3P_{n−1}\) \(+ P_{n−2}\)

Hence Option A



niks18
Thanks :)
Well starting from n=0 makes problem little simple :P

Added note just in case if someone else have other method than he can share that :) :)

[PS: i think i should try to avoid solving questions and posting solutions when i am in between 2 things :P :P ]

Kudos [?]: 80 [0], given: 65

Intern
Intern
avatar
B
Joined: 27 Nov 2016
Posts: 18

Kudos [?]: 14 [0], given: 9

GPA: 2.75
CAT Tests
Re: Let x and y be the solutions of the equation a^2+3a-1=0 [#permalink]

Show Tags

New post 17 Sep 2017, 00:12
Option:A
Put n =2 in the expression.
Since finding P0 and P1 isn't time consuming, we can easily reach to the answer within a minute.

+1 Kudos if it helped.
_________________

+1 Kudos if my post helps in any way :)

Kudos [?]: 14 [0], given: 9

Re: Let x and y be the solutions of the equation a^2+3a-1=0   [#permalink] 17 Sep 2017, 00:12
Display posts from previous: Sort by

Let x and y be the solutions of the equation a^2+3a-1=0

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  


GMAT Club MBA Forum Home| About| Terms and Conditions| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.